Semantic use of medical euphemisms in German (Eurasian Journal of Learning and Academic Teaching, 2023)
This article covers the semantic analysis of medical euphemisms. In this article, research on euphemisms in German journalism has shown that the use of these euphemisms in the field of medicine helps readers to understand texts faster and serves to embellish and soften difficult-to-speak information.